Early glass cell for polyamide preparation (1935)
General view of a glass cell used for the preparation of polyamides during the early stages of nylon production and research at the DuPont Experimental Station in Wilmington, Delaware. Predating the autoclave developed by Dr. Edgar W. Spanagel, glass cells such as this one served as a type of reactor used to combine adipic acid and hexamethylediamine in order to form nylon salt.
Keywords: Nylon; Scientific apparatus and instruments; E.I. du Pont de Nemours & Company. Experimental Station; E.I. du Pont de Nemours & Company; Chemical reactors